2018
DOI: 10.1093/nar/gkx1311
|View full text |Cite
|
Sign up to set email alerts
|

LncMAP: Pan-cancer atlas of long noncoding RNA-mediated transcriptional network perturbations

Abstract: Gene regulatory network perturbations contribute to the development and progression of cancer, however, molecular determinants that mediate transcriptional perturbations remain a fundamental challenge for cancer biology. We show that transcriptional perturbations are widely mediated by long noncoding RNAs (lncRNAs) via integration of genome-wide transcriptional regulation with paired lncRNA and gene expression profiles. Systematic construction of an LncRNA Modulator Atlas in Pan-cancer (LncMAP) reveals distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 62 publications
1
93
0
Order By: Relevance
“…With the development of next-generation sequencing technology, it is realized that the most part of human genome is transcribed to noncoding RNAs [2]. Of these newly discovered RNA regulatory elements, long noncoding RNAs (lncRNAs) have been demonstrated to play critical roles in diverse cellular processes [3][4][5]. LncRNAs can serve as signal mediators, scaffold or molecular decoys to function in epigenetic, transcriptional and posttranscriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing technology, it is realized that the most part of human genome is transcribed to noncoding RNAs [2]. Of these newly discovered RNA regulatory elements, long noncoding RNAs (lncRNAs) have been demonstrated to play critical roles in diverse cellular processes [3][4][5]. LncRNAs can serve as signal mediators, scaffold or molecular decoys to function in epigenetic, transcriptional and posttranscriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and our results shown above indicated that lncRNA is differentially expressed between TN breast cancer subtypes, thus lncRNA may be explored as a new class of clinical biomarkers for therapy response or targets for drug discovery (Arun et al ., ; Prabhakar et al ., ; Wu and Du, ). To identify drug‐related lncRNA in breast cancer, we explored the association of the LncKLHDC7B levels and drug activity with the lncMAP tool (Li et al ., ) (http://bio-bigdata.hrbmu.edu.cn/LncMAP/index.jsp), which computes the Spearman correlation coefficient between lncRNA expression and the half maximal inhibitory concentration (IC 50 ) values of 24 drugs approved for oncology purposes in TNBC cell lines. We observed a significant negative correlation between the expression of LncKLHDC7B and concentrations of lapatinib and paclitaxel (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Having demonstrated that ImmLnc can effectively identify immune-related lncRNAs, we next explored the application of ImmLnc for prioritizing cancer-related lncRNAs. Although an increasing number of lncRNAs have been identified by experimental and computational methods 3,37 , the identification of novel cancer lncRNAs based on large-scale experiments is expensive and time consuming. We hypothesized that if the lncRNA-pathway relationships can be observed in more cancer types, they are more likely to be involved in cancer.…”
Section: Identification Of Immune-related Lncrnas Across Cancer Typesmentioning
confidence: 99%